The Relationship between Sex Role Stereotypes, Domestic Violence Training, History of Law Enforcement Involvement, and Law Enforcement Officer's Perceptions of a Domestic Violence Incident - Schuch, Kristen M. (2002)
This study examined how police officers perceptions of a domestic violence situation are influenced by sex role stereotypes, domestic violence training and history of police intervention. Participants were police officers employed in sheriff's departments or city police departments. Officers received several surveys and a vignette describing a domestic violence scene. Officers were given one of two vignettes, one describing a situation in which there have been previous calls to the address and one in which this is the first call and were then asked several questions to assess their perceptions. Sex role stereotypes were assessed using the Sex Role Egalitarianism Scale. Results indicated a positive correlation between perceptions of the incident and scores on the sex role questionnaire. There was a significant difference between officers who received the first time call vignette and officers who received the repeated calls vignette on their scores on the marital roles subscale of the sex role questionnaire. Future research is needed to expand these results